Descriptive Study of Liver Hydatid Cyst in the Post Graduated Hospital Khost - Raoufi, Said Aref; Qadri, Abdullah; Hemat, Mohammad Qadir Shah; Nangialai, Nangialai (Journal for Research in Applied Sciences and Biotechnology, 2022)
Liver hydatid cyst is a parasitic disease whose life cycle involves carnivores. And humans can also get infected by swallowing of parasite eggs. This disease can affect both men and women. This disease does not have a severe course; therefore, it is often diagnosed in the mixed stages or when the patient performs abdominal ultrasound examinations due to some other health problems. This is the reason why most of the serious hydatid disease conditions occur. Since Afghanistan is an agricultural country and livestock farming is common there, the possibility and incidence of this disease is very high in human. This study is a descriptive study in the form of a case series, from the 1400/07/01 to 1401/06/31 (one-year duration), on 40 patients which have been treated in Khost post graduate Hospital. In 40 patients who have a hydatid cyst of the liver, 29 patients representing 72.5% of the cases are from the districts and 11 from the center of Khost representing 27.5%. according to age, the most cases occurred in people under 30 years of age (28 people), which make up 59.5 %, 7 people were between 30 and 50 years old, 17.5 % and 5 people were over 50 years old. Which is 12.5 %. From the point of view of gender, the most cases are women (27), which make up 67.5 %. And 13 men, which constitute 32.5 % of the cases. From the point of view of cyst size, 25 patients whose cyst size was less than 7 cm and 70 % of patients and 15 patients whose cyst size was more than 9 cm showed 30 % cases. Open surgery was performed on all the above patients (100 %). According to complications, 2 patients had cyst rupture, which was 5 %, and one patient had a obstructive jaundice, which was 2.5 %. Most of the cases of this disease occurred in women and people under the age of thirty. From the point of view of the place of residence, the incidents occur more in the suburban areas. All patients with hydatid cyst of the liver, when diagnosed and operated on time, recover quickly, but follow-up treatment was necessary.